Software-guided standardization of manual landmark data in medical images - Prüm, Hermann; Gerigk, Lars; Hintze, Christian; Thieke, Christian; Floca, Ralf (Zeitschrift für medizinische Physik, 2011)
It is crucial to evaluate registration algorithms in order to make them available in clinical practice. Several evaluation strategies have been proposed in the past, and one approach is to evaluate these algorithms with intrinsic anatomical landmarks identified by a health professional. The acquisition and handling of large amounts of these landmark data is a time-consuming task for the health professional, and it is vulnerable to errors and inconsistencies. Additionally, limited access to appropriate tools makes dealing with landmark data considerably more difficult. We introduce a strategy for the acquisition of landmarks for the landmark-based evaluation of registration algorithms and we present an ontology-driven software tool that assists the different partners involved to act according to that strategy. This tool provides the user with intrinsic knowledge of the registration problems, the possibility to conveniently make the acquired data available to further processing, and an easy-to-use graphical interface.